The Impact of Covid-19 on Academic Practice: A Dilemma-Driven Self-Study Inquiry at an Institution of Higher Learning - Tholani Tshuma (Research in Social Sciences and Technology, 2023)
This inquiry was a dilemma-driven, object-inquiry self-study. The study followed visual methodologies in unpacking the impact of Covid-19 on the practices of a practitioner at a rural university. During the Covid-19 pandemic, I was becoming increasingly dissatisfied with my daily practice as an academic because I struggled to locate my footing in what has been dubbed the ‘new normal’ about online student teaching and assessment. In my bid to investigate the dissatisfactions I faced due to Covid-19, I followed the self-study methodology, which entailed my engagement in reflexivity cycles, and feedback from critical friends. My critical friends played a crucial validation role during my data collection, analysis, and drawing of conclusions from multiple data forms that included journal entries and discussions with others. The collected data was thematically and analyzed from deductive to inductive perspective through the process of coding. This inquiry established that the outbreak of Covid-19 led to dilemmas of practice that stemmed from my being deskilled, techno and Covid-phobic; poor individual adaptability; inadequate TPKC; and the shortcomings of working as an isolated silo. It emerged that these dilemmas of practice escalated into professional traumas through working in isolated silos in virtual platforms. Thus, through making our challenges of practice public, we tend to benefit from the pool of probing expertise of others. Whilst the advent of Covid-19 posed unwelcome professional traumas, it was through the probing power of ‘the second voice’ that the over-shadowed professional growth opportunities in this pandemic induced ‘new normal’ was unveiled.